2000
DOI: 10.1177/0148607100024005261
|View full text |Cite
|
Sign up to set email alerts
|

Individual Neuropeptides Regulate Gut‐Associated Lymphoid Tissue Integrity, Intestinal Immunoglobulin A Levels, and Respiratory Antibacterial Immunity

Abstract: Supplementation of IV-TPN with CCK, gastrin, and NT prevents GALT atrophy, primarily in the distal bowel. Intestinal IgA levels improve but not to normal levels. CCK and gastrin reversed IV-TPN-induced effects on antibacterial pneumonia in immunized animals while NT did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…In experimental models, simultaneous administration of either gastrin or CCK or NT with TPN had a different and in each case beneficial effect on GALT [93]. NT is a 13-amino-acid peptide stored in granules in NT-containing cells (N-cells) which are scattered in the epithelial layers of the jejunum and ileum [94].…”
Section: Intestinal Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental models, simultaneous administration of either gastrin or CCK or NT with TPN had a different and in each case beneficial effect on GALT [93]. NT is a 13-amino-acid peptide stored in granules in NT-containing cells (N-cells) which are scattered in the epithelial layers of the jejunum and ileum [94].…”
Section: Intestinal Nervous Systemmentioning
confidence: 99%
“…Finally, the administration of CCK and gastrin, but not NT, restored the immune response against bacterial pneumonia. Enrichment of intravenous TPN with CCK, gastrin, and NT prevents GALT atrophy, especially in the distal bowel [93]. Of note, although each of these neuropeptides ameliorated the adverse effects of the lack of dietary stimulus in the lumen, only BBS completely inhibited such effects on GALT.…”
Section: Intestinal Nervous Systemmentioning
confidence: 99%
“…Our prior work demonstrated that cholecystokinin, gastrin, and neurotensin-neuropeptides released in response to bombesin administration-reduce atrophy of the GALT system in TPN-fed animals. 13 Cholecystokinin and gastrin produce more effects upon mucosal immunity than neurotensin. The novelty of the current study is that it demonstrates that the C-terminal heptapeptide of bombesin and GRP is sufficient to induce a cellular effect upon GALT cell mass.…”
Section: Resultsmentioning
confidence: 99%
“…Other neuropeptides including cholecystokinin and neurotensin also exert phenotypic changes upon the GALT but none appear as effective as BBS. 161 This is likely due to the effect of GRP, which stimulates downstream release of multiple neuropeptides by the ENS.…”
Section: Surrogates For Entmentioning
confidence: 99%